Carmen Blacker, The Japanese enlightenment: a study of the writings of Fukuzawa Yukichi. Cambridge University Press, Cambridge, Mass., 1964. 186 pp. (University of Cambridge, Oriental Publications, 10.) - Ota Mishima, María Elena (Estudios de Asia y África, 1968)
-